Investment in Accounting Information Systems, Financial Performance and Productivity of Malmquist and IFR as Intervening in the Banking and Financial Industry - Dewi, Nurul Hasanah Uswati; Rokhmania, Nur'aini (Jurnal ASET (Akuntansi Riset), 2021)
The purpose of this study was to examine the effect of investment in information systems in the banking industry and financial institutions as measured by IT capital expense on profitability as measured by return on assets and productivity as measured by the malmquist measurement, and how will it affect if it is intervening with disclosure of information through Internet Financial Reporting. This research method is quantitative using SPSS-assisted regression analysis. Research on the topic of productivity is usually carried out in manufacturing companies, but this research uses the banking industry and financial institutions.Based on the results of the study, it shows that investment in accounting information systems as measured by IT capital or investment in software or hardware has a strong influence on the level of profitability both directly and through disclosure of internet financial reporting (IFR). However, investment in IT in the banking industry and financial institutions has no effect on malmquist productivity. If through IFR, there is an influence between IT capital and malmquist productivity.